2019
DOI: 10.1101/766881
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The nuclear to cytoplasmic ratio directly regulates zygotic transcription inDrosophilathrough multiple modalities

Abstract: Early embryos must rapidly generate large numbers of cells to form an organism. Many species accomplish this through a series of rapid, reductive, and transcriptionally silent cleavage divisions. Previous work has demonstrated that before both cell cycle elongation and zygotic genome activation (ZGA), the number of divisions is regulated by the ratio of nuclear content to cytoplasm (N/C). To understand how the N/C ratio affects the timing of ZGA we directly assayed the behavior of several previously identified… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Control of the MBT by the N/C ratio is important in several species, including Drosophila and Xenopus 25,26,[35][36][37][38] but likely excluding zebrafish. [39][40][41][42] This density of DNA (as well as nuclear size 43,44 ) can directly or indirectly impact multiple aspects of the MBT, namely zygotic gene expression [45][46][47][48] and cell cycle control. 26,35,[49][50][51] Here, we have exploited the changes in nuclear positioning in shkl embryos to generate a continuous range of nuclear densities.…”
Section: Discussionmentioning
confidence: 99%
“…Control of the MBT by the N/C ratio is important in several species, including Drosophila and Xenopus 25,26,[35][36][37][38] but likely excluding zebrafish. [39][40][41][42] This density of DNA (as well as nuclear size 43,44 ) can directly or indirectly impact multiple aspects of the MBT, namely zygotic gene expression [45][46][47][48] and cell cycle control. 26,35,[49][50][51] Here, we have exploited the changes in nuclear positioning in shkl embryos to generate a continuous range of nuclear densities.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, live imaging of nascent transcripts showed that the arrested embryos exhibited high levels of zygotic transcription earlier than control embryos, and the later patterning and declining of transcription also paralleled that of the control embryo. A recent preprint has used the MS2::MCP-GFP system to analyze the zygotic transcription of a handful of genes including kni at the MBT as well [38]. By using the integral of fluorescent intensity over time as a surrogate measure of cumulative mRNA production, they similarly found that the zygotic expression level of kni is insensitive to N/C but dependent on interphase length.…”
Section: Zygotic Transcription Is Patterned In Cell Cycle-arrested Emmentioning
confidence: 99%
“…Third, N/C modulated the degradation of Cdc25 Twine , a phosphatase that activates cyclin/Cdk1 by removing its inhibitory phosphorylation and thus regulates cell cycle remodeling at the MBT [ 35 37 ]. Lastly, a more recent preprint suggested that N/C could directly influence the kinetics of transcription activation as well as the probability of transcription initiation for certain genes [ 38 ].…”
Section: Introductionmentioning
confidence: 99%